Gender equity in hemophilia: need for healthcare, familial, and societal advocacy - Gualtierotti, Roberta; Garagiola, Isabella; Mortarino, Mimosa; Spena, Silvia; Romero-Lux, Olivia; Peyvandi, Flora (Frontiers in Medicine, 2024)
Hemophilia is a rare bleeding disorder caused by a genetic defect on chromosome X. It is inherited as an X-linked trait, and hence, it is more frequently diagnosed in males, whereas women have been traditionally considered only as carriers of the disease. However, the role of women in families of patients with hemophilia is pivotal. As mothers, sisters, daughters, and female partners of patients with hemophilia, they play a central role in the management of the patient, considering healthcare, social, and familial aspects, . However, the role of women for male patients with hemophilia is pivotal. As mothers, sisters, daughters and female partners of patients with hemophilia, they play a central role in the management of the patient considering healthcare, social and familial aspects, but they might also be affected by the disease as well, particularly in regions where consanguinity is frequent.This paper aims to explore the involvement of women in hemophilia, including their carrier status, bleeding symptoms, treatment challenges, and psychosocial impact not only related to male patients, but also as patients affected with hemophilia themselves.We advocate health equity, equal access to healthcare for men and women with hemophilia and dedicated resources to improve the unique needs of the women dealing with hemophilia, ultimately leading to improved care and quality of life.